La arquitectura sustentable: una respuesta para la vivienda de interés social en la ciudad de Tunja (2021)
This article aims to carry out an analysis about the relevance of sustainable architecture in our Latin American context, specifically focused on social interest housing in the city of Tunja. So that a comparison has been made of the effective way with which the architect Alejandro Aravena of the solution for housing for people affected with respect to the real problems of the housing complexes “Torres del Parque” and “La Estancia del Roble”.